2015
DOI: 10.1016/j.jmoldx.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of a Cytokine and IFN-γ–Induced Chemokine mRNA Assay after Mycobacterium tuberculosis–Specific Antigen Stimulation in Whole Blood from Infected Individuals

Abstract: Interferon (IFN)-γ release assays have limited sensitivity and cannot differentiate between active tuberculosis (TB) disease and latent TB infection (LTBI). Numerous cytokines and regulator factors have been implicated in the pathogenesis and control of Mycobacterium tuberculosis infection. Additional cytokines and chemokines associated with M. tuberculosis infection may improve the performance of IFN-γ release assays. We developed a real-time RT-PCR TaqMan assay for targeting levels of eight human targets [IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…Lower IL-2/IFN-γ secretion [7,26] and a relative shift from IL-2 towards IFN-γ production were determined in ATB compared to LTBI or successfully treated TB subjects [57,25,26]. Similar observations were also made with other Th1 related cytokines, IP-10, MIG, TNF-α [5,7]. Analysis of T cell response against ESAT-6/CFP-10 at single cell level using flow cytometry were also in line with these results [13,15,2729].…”
Section: Discussionmentioning
confidence: 99%
“…Lower IL-2/IFN-γ secretion [7,26] and a relative shift from IL-2 towards IFN-γ production were determined in ATB compared to LTBI or successfully treated TB subjects [57,25,26]. Similar observations were also made with other Th1 related cytokines, IP-10, MIG, TNF-α [5,7]. Analysis of T cell response against ESAT-6/CFP-10 at single cell level using flow cytometry were also in line with these results [13,15,2729].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to more accurately distinguish between these two stages, the selective combination of immune response genes has been under study. Among them, the protein levels of CXCL10 (IP-10; Tonby et al, 2015; Wergeland et al, 2015; Xiong et al, 2016; regulated under IFN-γ) and levels of mRNA Kim et al, 2015 or protein (Jeong et al, 2015; Lee et al, 2015a) for CXCL9, CXCL10, and CXCL11 have been pointed out by other researchers. These studies were mostly performed with blood mononuclear cells after stimulation with Mtb-specific antigens.…”
Section: Discussionmentioning
confidence: 94%
“…Previous study confirmed that five genes (IFN-γ, TNF-α, IL-2R, CXCL9, and CXCL10) could be used for the detection of Mtb infection, including active PTB disease and LTB. The sensitivity of each gene was above to 80% [17]. The gene network profile provided more potential for diagnostic biomarkers selection.…”
Section: Discussionmentioning
confidence: 95%